Kunst van heden in België. - Sint-Pietersabdij, Gent (Gent : Sint-Pietersabdij, 1965)
Aebly, Albert ; Alechinsky, Pierre ; Anthoons, Willy ; Antoine, Paul ; Arnould, Marcel ; Baibay, Gilbert ; Beirens, Vic ; Billet, Yves ; De Boeck, Felix ; Boel, Maurice ; Bronkart, Silvin ; Burssens, Jan ; Bury, Pol ; Camus, Gustave ; Collignon, Georges ; Comhaire, Georges ; Creuz, Serge ; Delahaut, Jo ; Delvaux, Paul ; Denaeyer, Roland ; Depuydt, Stefaan ; Devos, Pierre ; Dille, Frans ; Donnay, Jean ; Donnay, Paul ; Van Doorslaer, Etienne (Maur-Etienne) ; Dudant, Roger ; Van Elzen, Staf ; Gailliard, Jean-Jacques ; Gaudaen, Gerard ; Geenens, Robert ; Geurden, Elisabeth ; Ghysels, Jean-Pierre ; Gibon, Marcel ; Godderis, Jack ; Grard, Georges ; De Grave, Jean-Jacques ; Graverol, Jane ; Guiette, René ; Van Gysegem, Paul ; Hanrez, Paul ; Heerbrandt, Henri ; Heylen, Jan ; Holmens, Gerard ; Van Hoorde, Ernest ; Hubert, Marcel ; Ivanovsky, Elisabeth ; Jacob, roger ; Jans, Jos ; Ketelslegers, Robert ; Laffineur, Marc ; Lahaut, Pierre ; Landuyt, Octave ; Leblanc, Walter ; Lecomte, Louis Alphonse ; Lemaire, Mady ; Van Lint, Louis ; Lismonde ; Londot, Louis-Marie ; Macken, Mark ; De Maeyer, Jacky ; Magritte, René ; Malfait, Hubert ; Mara, Pol ; Marchoul, Gustave ; Martini, Remo ; Van Melkebeke, Jacques ; Mendelson, Marc ; Milo, Jean ; Minne, Joris ; de Montpellier, Béatrice ; Mortier, Antoine ; Nolens, Paule ; Notebaert, Marcel ; Opsomer, Isidore ; Van Paemel, Jules ; Pion, Jean-Louis ; Poot, Rik ; Ransy, Jean ; Rets, Jean ; Rhaye, Yves ; De Rouck, Charles ; Roulin, Félix ; Salkin, Emile ; Saverys, Albert ; Scevenels, Auguste ; Schmetz, Betty ; Servranckx, Victor ; Seuphor, Michel ; Silvestre, Armand ; Slabbinck, Rik ; Somville, Roger ; Stievenart, Michel ; Stobbaerts, Marcel ; Strebelle, Jean-Marie ; De Sutter, Jules ; van Thienen, Paul ; Toussaint, André ; etc.
Nederlands
Kunst van heden in België, Centrum voor kunstambachten - gewezen Sint-Pietersabdij Gent, 23.10. - 15.11.1965
boek